Eugenija Šimkūnaitė and the “Case of Indraja” - Kadžytė, Gražina (Tautosakos darbai, 2020)
In 2020, the 100th anniversary of an extraordinary personality – assistant professor in natural sciences, ethnographer, herbalist and public figure Eugenija Šimkūnaitė (1920–1996) is celebrated. Along with her scholarly merits, Šimkūnaitė was a tireless promoter of ethnic culture, campaigning for various contemporary applications of the heritage. She consulted archeologists and activists of regional studies, participated in organizing the midsummer festival Rasos in Kernavė. From the folkloristic perspective, the most intriguing is the “case of Indraja”, related to Šimkūnaitė’s idea of providing her native country with a mythic ancestress Indraja. Academy professor Leonardas Sauka has discussed this case in his study on folklore and fakelore (1983). Supported by various intellectuals, Šimkūnaitė attempted introducing Indraja into the folklore circulation, primarily using her publications in popular periodicals. In 1999, the charity foundation established by Šimkūnaitė’s students and friends published a collection of her authorized fairy tales “Indraja, the Daughter of Sun”. Since then, a double myth started spreading: both of the fictional figure Indraja, and its creator – the healer and the wizard. This process was also influenced by a documentary “The Healer” (1975), and by Šimkūnaitė’s personalization at the Museum of History of Lithuanian Medicine and Pharmacy. Šimkūnaitė has been included into the list of one hundred of the most influential people of Lithuania (97th place), the herbal processing company in Švenčionys produces special herbal mixtures following her recipes. In her native place Tauragnai, a cherry-tree garden was planted in result of a numerous social campaign. In Vilnius, a memorial stone with herbal ornaments bears the Healer’s prayer to the Sun. Šimkūnaitė was undoubtedly an exceptional character, and her relationship with folklore, although controversial, was always intriguing.